“Tia, você me adota?” : o abrigo e a escola na constituição subjetiva da criança sob tutela do Estado - Tavares, Nelma (2014)
The aim of this study was to discuss how foster care and schooling impact the child’s subjectivity. Our research was grounded on the socio-historical theories of human development, particularly trough the contributions of Lev Vygotsky, Henri Wallon and Mikhail Bakhtin. The research was carried out at Casa-Lar Santa Cecília, a foster care facility for children in state custody, and in a public elementary school (3rd grade), both located in the city of Vila Velha. Two children, a boy (Noah) and girl (Sofia) both aged 10, were investigated and a case study research design was adopted to allow for a fuller understanding of their experience. Data collection consisted of participant observation together with semi-structured interviews with foster care and school workers involved. Family disruptions, followed by foster care intervention, almost inevitably leave the children indelibly scarred. In both cases, feelings of emptiness and extreme sadness were observed. We found the physical marks of abuse on Sofia’s body, the psychological ones in her silence and in the long, inerasable pain of her past life. Her expectations centered on adoption or any other life but the foster care. The gradual disintegration of Noah’s destitute family, the adoption of his brothers, his suffering and homesickness were expressed by crying and anger, rudeness and impatience with his classmates – these were his way of dealing with so many losses he had experienced. On the other hand, school was seen by the two children as a meaningful, hopeful place for becoming full-fledged students; the interaction with others brought them satisfaction and, to some extent, helped their development. We observed in these two students the voices and feelings of their mates, and the impact they had in the construction of subjectivity of Sofia and Noah; in other words, they demonstrated a heightened sense of belonging to a social peer group and of having a proper place in school life.